Evaluation of Drug Management of Pharmacy Installation at Universitas Sumatera Utara Hospital - Sari, Syilvi Rinda; Khairunnisa; Aminah Dalimunthe (Indonesian Journal of Pharmaceutical and Clinical Research, 2020)
Evaluation of Drug Management of Pharmacy Installation at Universitas Sumatera Utara Hospital